Silver and copper nanostructured particles recovered from metalized plastic waste for antibacterial applications. Issue 4 (August 2020) - Elsayed, D.M.; Abdelbasir, S.M.; Abdel-Ghafar, H.M.; Salah, B.A.; Sayed, S.A.
Graphical abstract: Abstract: This work presents a method of recycling silver and copper from metalized acrylonitrile butadiene styrene (ABS) plastic wastes as nanostructured particles. Metallized ABS plastics were first leached in nitric acid for dissolving silver and copper. More than 87% of Ag and 92% of Cu in the metalized ABS plastic waste were lixiviated in 3.2 M HNO3 under the leaching conditions of solid/liquid ratio 1:30 and stirring rate of 300 rpm for 2 h at room temperature. The leaching kinetics have been examined and the reactions were deemed diffusion controlled. The activation energies were calculated from Arrhenius plot to equal 36 and 27.84 KJ/mole for Ag and Cu leaching, respectively. Ag, Cu, and bimetallic Ag/Cu nanoparticles were separately synthesized from the nitric acid leachant by controlling the pH of the solution and using ascorbic acid in the presence of chitosan as a stabilizer at 60 °C. The average sizes of Ag, Cu, and Ag/Cu nanoparticles were around 50–80 nm, as determined through TEM images. Bactericidal activities of Ag, Cu and Ag/Cu were tested versus some common infectious gram-negative and gram-positive bacteria. Ag/Cu nanoparticles revealed the highest inhibition zone at concentration 10 mg ml −1 versus gram-negative bacteria.